Continuous Stimulation of Sacral Roots in the Treatment of Urinary Pathologies and Fecal: Clinical Evaluation of a Series of 18 Patients Implanted - Acevedo González, Juan Carlos; Hospital Universitario San Ignacio (Pontificia Universidad Javeriana, 2013)
Introduction: Sphincter control pathologies undermine the Quality of Life (QoL).Objectives: To assess the results of the treatment with sacral nerve stimulation in patients with urinary and fecal incontinence and with sexual dysfunction.Results: From 2007 to 2012, electrodes were implanted in 18 patients for sacral nerve stimulation (6 had urge urinary incontinence; 4, mixed incontinence; 4, urgency frequency incontinence; 2, urinary retention; 2, fecal incontinence, and 1, retrograde ejaculation). We assess records of urinary or fecal leakage and questionnaires on QoL.Conclusions: The best results were presented by the urgency frequency patients (they all improved), by the fecal incontinence group and it amazes the good results obtained by the patient with retrograde ejaculation. In conclusion, sacral nerve stimulation is an effective technique for the treatment of illnesses that produce urinary or fecal incontinence obtaining an improvement of QoL over 50 %.